Bioremediation - An alternate utility of cloned lignin peroxidase from Phanerochaete chrysosporium * - MONICA, C LOGESWARI; TIRUMURUGAAN, K G; VIJAYARANI, K; CHANDRASEKARAN, C; KUMANAN, K (The Indian Journal of Animal Sciences, 2013)
Physical, chemical and biological methods were explored to identify a practicable solution for bioremediation. Biological methods always have remained attractive and in this context we targeted Phanerochaete chrysosporium a wood degrading fungi that is not only well known for its degradation ability but also a producer of lignin modifying enzymes. This fungi was grown under nitrogen limiting conditions and the peak ligninase activity could be observed on the fourth day in the culture supernatant as detected by methylene blue and veratryl alcohol assay. The full-length gene of the major isoform of lignin peroxidase (LiP) the LiP-H8 was amplified and cloned into pYES-DEST52 expression vector. The active expressible LiP-H8 expression clone was confirmed by employing an agar plate incorporated with methylene blue which resulted in a zone of clearance after 48 h indicating its degradation capability. Further studies by transformation of the confirmed LiP-H8 clone into laboratory strains of Saccharomyces cerevisiae and assessing the enzyme activity would determine the future implications of this recombinant lignin peroxidase.